Protective efficacy of Murraya koenigii aqueous extract against monosodium glutamate-induced hepatotoxicity in Wistar rats (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2023)
The present work was designed to study the potential effect of antioxidant rich aqueous extract of Murraya koenigii (AE-MK) on monosodium glutamate-induced hepatotoxicity in Wistar rats. The study was conducted on thirty adult Wistar rats, classified into six groups. MSG (1000 mg/kg, p.o) was administered to induce hepatotoxicity. The MSG treated group showed significant (P ˂0.05) increase in % change in body weight, relative organ weight, SOD, MDA, cholesterol, bilirubin, triglycerides, LDL levels; and AST, ALT activity while significant (P